Ethnicity and constitutional reform in South Asia - Iftekharuzzaman; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (New Delhi : Manohar, 1998)
Comprises papers presented at an international seminar organized by Regional Centre for Strategic Studies in Colombo on 19-20 February 1995.
"Regional Centre for Strategic Studies, Colombo."
Includes bibliographical references.
Keywords: Ethnicity -- South Asia; Constitutional history -- South Asia; South Asia -- Politics and government